Injury prevention for shod vs. minimal footwear/barefoot runners: Exploratory study during competition and laboratory - Daumer, M.; Kleinmond, C.; Stolle, C.; Fsching, M.; Walther, M. (International Calgary Running Symposium, August 14-17, 2014, 2014)
INTRODUCTION: Recently the number of long distance runners wearing minimal footwear or running barefoot (MF/B) increased considerably. There is an on-going debate about benefits and risks of running in MF/B compared to conventional shoes (SH) [1,2]. PURPOSE: Purpose of this study was to investigate the effect of different types of shoes and different running techniques on acceleration of centre of gravity (CG). METHODS: Acceleration data (AD) was assessed by a mobile accelerometer (actibelt¢ç) from 29 participants in a 24h run (1 male B 128km; 1 female SH 92km; 12 SH relay 323km; 15 MF/B relay 243km) and the author MD himself from 4 mountain runs (2 MF/B 54km, 2 MF/B 19km), 3 marathons (1 SH, 2 MF/B, 42km) and 2 half marathons (MF/B 21km). 3 runners were investigated during a treadmill test (TMT) (high speed camera system, coupled wireless stream of AD). AD was analysed with standardized algorithms using RESULTS: Analysable AD was retrieved during the author.s runs and during the 24h run from both single runners and the MF/B relay team. Few useful recordings could be done in SH team (compliance problems). By analysing AD a general tendency for increased step frequency (SF) and reduced stride length (SL) in MF/B vs. SH can be confirmed. In the 24h run both SH and MF/B controlled gait speed via SF, correlation to SL was less obvious. TMT provided smoother curves for MF/B particularly in the up down AD and less power in the high frequencies in the Fourier spectrum. No severe injuries occurred (minor: toe nail off, cut in sole & DOMS, blister). Another individual known by author MD developed severe pain in one metatarsal joint after having changed to MF/B that needed surgery twice and led to severe persistent problems with running ability. CONCLUSION: Mobile accelerometry is a feasible technology to explore different running patterns outside of gait laboratories. The results show that MF/B was typically associated with different running patterns indicating a more effective use of evolutionary damping system. Well trained MF/B can run long distances without injuries, but others may face the risk of severe injury. More research is needed to translate biomechanical findings from laboratory and empirically observed injury rates into individual evidence based recommendations about running style and footwear.